Dietary reference intakes for sodium and potassium - Stallings, Virginia A.; Quirk, Meghan (Of the National Academies of Sciences, Engineering, and Medicine (U.S.)); Oria, Maria (The National Academies Press, 2019)
As essential nutrients, sodium and potassium contribute to the fundamentals of physiology and pathology of human health and disease. In clinical settings, these are two important blood electrolytes, are frequently measured and influence care decisions. Yet, blood electrolyte concentrations are usually not influenced by dietary intake, as kidney and hormone systems carefully regulate blood values. Over the years, increasing evidence suggests that sodium and potassium intake patterns of children and adults influence long-term population health mostly through complex relationships among dietary intake, blood pressure and cardiovascular health. The public health importance of understanding these relationships, based upon the best available evidence and establishing recommendations to support the development of population clinical practice guidelines and medical care of patients is clear. This report reviews evidence on the relationship between sodium and potassium intakes and indicators of adequacy, toxicity, and chronic disease. It updates the Dietary Reference Intakes (DRIs) using an expanded DRI model that includes consideration of chronic disease endpoints, and outlines research gaps to address the uncertainties identified in the process of deriving the reference values and evaluating public health implications.
Keywords: Cardiovascular system -- Diseases.; Hypertension -- Risk assessment.; Sodium in the body -- Research.; Potassium in the body -- Research.; Diet in disease -- Research.; Chronic diseases -- Physiological aspects.; Nutrition.; Recommended Dietary Allowances; Sodium, Dietary; Potassium, Dietary; Nutritional Physiological Phenomena; Chronic Disease -- prevention & control; United States; Cardiovascular Diseases; Appareil cardiovasculaire -- Maladies.; Hypertension artérielle -- Évaluation du risque.; Sodium dans l'organisme -- Recherche.; Potassium dans l'organisme -- Recherche.; Régimes alimentaires -- Recherche.; Maladies chroniques -- Aspect physiologique.; Nutrition; Cardiovascular system -- Diseases; Diet in disease -- Research